Quantitative investigation on the stability of salt cavity gas storage with multiple interlayers above the cavity roof. (1st December 2021) - Li, Depeng; Liu, Wei; Jiang, Deyi; Chen, Jie; Fan, Jinyang; Qiao, Weibiao
Highlights: It is suggested to increase the thickness of the rock salt roof to ensure the stability of the salt cavern gas storage when there are multiple interlayers above the cavern roof. Under different geological and operating conditions, the waist of the storage and the part that intersects the interlayer deforms largely and receives greater stress. When the buried depth of the salt cavern gas storage increases, the minimum operating pressure inside it needs to be increased accordingly. The thickness of the rock salt roof of the salt cavern gas storage at different buried depths has little effect on its stability, but there is a risk of leakage when the roof thickness is small. Quantitative analysis shows that the buried depth and minimum operating pressure of the salt cavern gas storage are the key factors affecting its stability. Abstract: For the sake of safety and stability, a salt roof with certain thickness is usually designed above the cavity. While some rock salt often contains multi-interlayers above the cavity roof in China, which brings new challenges to designing salt roof thickness and evaluating cavity stability. On this basis, the factors affecting the stability of cavity with multiple interlayers above cavity roof is investigated. Combining single factor sensitivity analysis and analytic hierarchy process, the influence of each factor on cavity stability and roof deformation is quantitatively analyzed. Numerical simulation results show that when there are multiple interlayers above cavity roof, the stress and deformation of the cavity are increased compared with general conditions. The rock salt roof thickness has little effect on the stability of the cavity, but the cavity tightness is at risk when it is small. When the operating pressure is setting reasonably, the rock salt roof thickness should be greater than 11 m at around 1000 m deep and 17 m at about 2000 m deep. When the depth of the cavity is less than 1700 m and greater than 2000 m, the minimum operating pressure should be 0.3 and 0.4 times of the gravity stress at the depth of cavity roof. The change of the interlayers stiffness has a little impact on the stability of the cavity. The quantitative analysis indicates that the minimum operating pressure and buried depth are two critical factors that need special attention to ensure the stable operation of the salt cavity gas storage.